2016
DOI: 10.1128/jcm.00147-16
|View full text |Cite
|
Sign up to set email alerts
|

GenoType NTM-DR for Identifying Mycobacterium abscessus Subspecies and Determining Molecular Resistance

Abstract: bWe studied the performance of a new line probe assay for identifying the subspecies and determining the macrolide and aminoglycoside resistance levels of 50 Mycobacterium abscessus isolates. Agreement of GenoType NTM-DR results with sequencing and phenotypic resistance results was 92% for subspecies identification and 98% for determining molecular and phenotypic resistance. The Mycobacterium abscessus complex is divided into three subspecies: M. abscessus subsp. abscessus, M. abscessus subsp. massiliense, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 12 publications
2
26
1
2
Order By: Relevance
“…GenoType® NTM DR showed concordance with pDST in 94% for Clarithromycin resistance and in 94% for Amikacin resistance, improving to 98% and 96%, respectively, after repeat pDST. Similar results have recently been published by Kehrmann et al [18] and Mougari et al [19], however discordance of subspecies identification or resistance results did not take into account WGS data.…”
Section: Discussionsupporting
confidence: 87%
“…GenoType® NTM DR showed concordance with pDST in 94% for Clarithromycin resistance and in 94% for Amikacin resistance, improving to 98% and 96%, respectively, after repeat pDST. Similar results have recently been published by Kehrmann et al [18] and Mougari et al [19], however discordance of subspecies identification or resistance results did not take into account WGS data.…”
Section: Discussionsupporting
confidence: 87%
“…All isolates which had any mutation of position 2269, 2270, or 2271 (Escherichia coli numbering, positions 2057, 2058, and 2059, respectively) in rrl were resistant to clarithromycin ( We did not observe any isolates with an rrl mutation which also harbored a T28C mutation in erm (41). Where this occurred in isolates reported in the literature, they were always resistant (15,16). Of 37 isolates with a T28C mutation in erm (41) and no other relevant mutations, 84% (31/37) were susceptible to clarithromycin, 11% (4/31) had intermediate susceptibility, and 5% (2/31) were resistant.…”
Section: Resultsmentioning
confidence: 65%
“…http://dx.doi.org/10.1101/251918 doi: bioRxiv preprint first posted online Jan. 24, 2018; C1409T and G1491T were reported as causing resistance. [18][19][20] One article described rpsL as being important for aminoglycoside resistance in M. abscessus , but no specific SNPs were identified by the authors. 21 For ciprofloxacin, mutations in gyrA amino acid positions 92 and 96 and gyrB position 492 ( M. abscessus numbering) were associated with resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly a recent study showed the Hain GenoType NTM-DR line probe assay incorrectly predicted subspecies in 8% of samples, presumably because it lacks the whole genome resolution provided by sequencing and is vulnerable to between species recombination. 18 Despite analysing all mutations occurring in erm(41) and rrl for the full collection of genomes, we were unable to predict all clarithromycin resistance. This may be because there are other genes implicated or due to unreliable DST results.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 88%